Analisis korelasi antara kepuasan perkuliahan online dan efektivitas belajar mahasiswa kimia 2024 UIN Malang menggunakan software minitab - Muthola’ah, Rina Alifatul (Maliki Interdisciplinary Journal, 2025)
In the learning process, the use of technology has a significant impact on Chemistry students at UIN Malang, Class of 2024. Studenst satisfaction with online classes is believed to influence learning effectiveness. This study analyzes the correlation between two variables: student satisfaction with online classes (X) and learning effectiveness (Y), using Minitab software. Data were collected through a Google Form survey measuring student satisfaction with online lectures and their perceptions of learning effectiveness. The analysis indicates a weak negative correlation (r=−0.373;p>0.05) between student satisfaction with online classes and learning effectiveness. Further studies are needed to explore additional variables that may influence student satisfaction with online classes and learning effectiveness.